Variation av kobolt, selen och koppar inom och mellan fårbesättningar i Uppland - Sundström, Elin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2018)
Poisoning and deficiency of different microminerals occurs in Swedish sheep herds. Some breeds are more sensitive than others to suffer due to various metabolic functions. Another reason for deficiency or poisoning may be insufficient feeding space. The aim of this study was to investigate the variation of the microminerals Se, Co and Cu within and between sheep herds in Uppland and if this variation can be linked to factors such as sex and age The study showed that the variation in the concentration of the microminerals Se, Co and Cu in livers from slaughtered animals was greater between the animals within a herd than among different herds. In this study, none of the sampled animals suffered from a deficiency of any of the microminerals and the risk of poisoning was seen only due to high levels of Cu. High values of Cu were observed in all herds. No significant difference between adult animals and lamb or between sex could be detected.